PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN SUBSEKTOR FARMASI 2017-2021) - Yahya Wijayanto, Adelya; Irawati, Zulfa (Jurnal Manajemen, 2024)
This research investigates how profitability, liquidity, and leverage impact the value of companies within the pharmaceutical subsector over the period 2017-2021. This research seeks to investigate and clarify the impacts, both singularly and jointly, of profitability, liquidity, and leverage on the valuation of companies within the pharmaceutical subsector throughout the period from 2017 to 2021. This study utilized secondary data, specifically the Financial Statements of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The impact of independent variables, including Profitability, Liquidity, and Leverage, on the dependent variable, represented by the company's value measured by the price-to-book value (PBV) metric, was evaluated using SPSS software version 25. This research's findings indicate that the profitability variable does not partially impact the Value of the Company. The Value of the Company is demonstrated to remain unaffected by profitability levels, as determined through the Return On Assets metric. Conversely, the liquidity variable is found to have a positive partial effect on the Value of the Company. Similarly, a positive partial impact originating from the leverage variable on the Value of the Company is noted